Training & Rehabilitation - Franz A; 2; Becker J; Behringer M; Mayer C; Bittersohl B; Krauspe R; Zilkens C; 2 (Deutsche Zeitschrift für Sportmedizin, 2019)
Osteoarthritis (OA) of the hip and knee joint is a common disease worldwide and is associated with chronic disability and progressive pain. Currently, themost suitable treatment method in end-stage OA is surgical restoration by total joint replacement (TJR). In this regard, patients suffering from end-stage OA and waiting forTJR intervention are also affected by extensively impaired skeletal muscle health. This is characterized by progressive muscle atrophy, strength decline and associated deficits in neuromuscular activation. Unfortunately the importance of skeletal muscle health, as a predictor for a successful muscular and functional recovery, is clinically underrepresented in medical indication and preoperative diagnostics. Therefore, this review aims to describe patients pre, peri and postoperative muscle health during the whole process of aTJR intervention. Additionally, underlying mechanisms and potential perioperative stressors, which may be responsible for impaired muscular physiology after TJR, will be described. As a second purpose, this review illustrates the potential impact of preoperative exercise interventions by challenging the better in, better out approach in TJR therapy. KEY WORDS: Muscle Atrophy, Total Knee Arthroplasty, Total Hip Arthroplasty, Preoperative Intervention, Arthrogenic Muscle Inhibition